Mr. Herbert Spencer and the Land Restoration League. [Correspondence between Mr. Spencer and the general secretary of the League (= F. Verinder)] (English Land Restoration League, 1894)
Proof. Mostly repr.: Daily Chronicle. 1894, August, September and October.